The Influence of Amount Traveler's Regional Original Income Through Entertainment Tax, Hotel Tax, and Restaurant Tax Regency/City in Aceh Province - Nadirsyah; Fitriyadi Firman; Ridwan (PT Inovasi Pratama Internasional, 2024)
This study examines the impact of sources of tourists on local revenue (PAD) through entertainment tax, hotel tax and district/ cit restaurant tax in Aceh province for the period 2013-2017. Sample was obtained using all population which are districts/cities in Aceh province as many as 92 observations. The type of data used in this research is secondary data. The findings showed that number of tourists has no effect on PAD. This is because the main source of PAD does not come from the number of tourists alone but also comes from other local revenue receipts so that the number of tourists does not directly affect PAD. On the other hand, the number of tourists affects entertainment tax, hotel tax, and restaurant tax in the districts/cities of Aceh province. A number of tourists are assumed to spend on financial satisfaction in traveling which is directly followed by spending on entertainment taxes, hotel taxes, and restaurant taxes. Furthermore, entertainment tax, hotel tax, and restaurant tax have no contribution as an intervening variable on the effect of number of tourists on PAD.